UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU PAUD MELALUI PENYELENGGARAAN PROGRAM INKLUSIF DI TK AISYIYAH II CIMAHI - sutriawati, Sri; Windarsih, Chandra Asri (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Inclusive education is one of the non-discriminatory education reforms, equating basic rights to change the system from segregation to integration. Efforts to improve and readiness of professional teachers need concrete actions that can support the implementation of inclusive programs in PAUD. Formation and development of professional attitudes through training programs, training, TOT, workshops, lectures, seminars and development of early childhood teachers. The problem is "how the institution attempts to improve the professional competence of PAUD teachers through the implementation of an inclusive program at TK Aisysyiyah II Cimahi". The method used in this research is descriptive method with the consideration that this method is a method of research by describing events that exist in the present or that are happening. Professionalism competencies carried out are with knowledge, understanding, abilities, values, attitudes and interests without forgetting the student domain, content, instruction, assessment, learning environment, collaboration, and professionalism. Having professional competence can provide an opportunity for inclusive children to develop optimally. The shortcomings in handling that are not yet uniform, material that has not been focused, have not modified the personal curriculum still together, and there is still limited knowledge about inclusive children.        Pendidikan inklusif merupakan salah satu reformasi pendidikan yang nondiskriminatif, menyamakan hak-hak dasar merubah sistem dari segregasi menjadi integrasi. Upaya meningkatkan dan kesiapan guru yang profesional perlu adanya tindakan nyata yang dapat mendukung terselenggaranya program inklusif di PAUD. Pembentukan dan pengembangan sikap professional tersebut melalui program pelatihan, diklat, TOT, workshop, saresehan, seminar dan pengembangan guru PAUD. Permasalahannya “ bagaimana upaya lembaga dalam meningkatkan kompetensi profesional guru PAUD melalui penyelenggaraan program inklusif di TK Aisysyiyah II Cimahi”. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pertimbangan bahwa metode ini merupakan cara penelitian dengan menggambarkan peristiwa yang ada pada masa sekarang atau yang sedang terjadi. Kompetensi profesionalisme yang dilakukan adalah dengan pengetahuan, pemahaman, kemampuan, nilai, sikap dan minat tanpa melupakan domain student, contant, instruction, assesment, learning environment, collaboration, dan profesionalism. Dengan memiliki kompetensi yang profesional dapat memberikan kesempatan kepada anak inklusif kemandiriannya berkembang optimal. Adapun kekurangannya dalam penanganan yang belum seragam, materi yang belum terfokus, belum memodifikasi kurikulum personal masih bersamaan, dan masih terbatasnya pengetahuan tentang anak inklusif.